Indeks Bahaya dan Upaya Mitigasi Bencana Gelombang Ekstrim dan Abrasi di Wilayah Kecamatan Teluk Pakedai - Maulana, Iqbal; Meirany, Jasisca; Lestari, Arfena Deah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Coastal areas face threats from hydro-oceanographic activities and human actions, leading to disasters such as extreme waves and coastal erosion. In Indonesia, particularly in Teluk Pakedai sub-district, these issues are prominent. Effective mitigation strategies tailored to the region's characteristics are essential. This research aims to analyze extreme wave and abrasion threats in Teluk Pakedai and develop mitigation plans. Using the Indeks Ancaman Bahaya Gelombang Ekstrim dan Abrasi (GEA) method outlined in BNPB's 2012 guidelines, factors like wave height, ocean currents, beach typology, vegetation, and coastline shape will be assessed and mapped using ArcGIS. From 2018-2023, significant erosion and accretion were observed, with the highest erosion in Kuala Karang Village (16.93 Ha) and the most accretion in Tanjung Bunga Village (57.79 Ha). Seven villages face medium to high danger from these threats. Recommended mitigation strategies include mangrove planting, constructing breakwaters, establishing early warning systems, and enhancing public awareness of extreme wave and abrasion risks.